MOLECULAR MECHANISMS ASSOCIATED WITH ACUTE MYELOID LEUKEMIA: REVIEW ARTICLE - Al Asseri, Mohammed; Al Khatib, Ahed J; Qasem, A’aesha M; Hamadi, Abdullah Yahya; Laiche, Fatima (European Scientific Journal, ESJ, 2013)
The present review article purposes to introduce the molecular mechanisms underlying acute myeloid leukemia (AML). An overview of AML was introduced including its classification, therapeutic options and the roles of mutations in p53 and WT1 genes. The possibility of molecular targeting therapies was also discussed. The efforts of many researchers concerning AML were taken into consideration during this review. We also pointed to the various roles of WT1 gene as suppressor or oncogene. The important relationship between p53 gene and WT1 gene was highlighted so that when WT1 gene stabilizes p53, the pathological picture concerning p53 if being mutated or not should be reconsidered again.